Socioeconomic factors influencing smallholder farmers’ willingness to cultivate neglected legumes and their selection of suitable planting dates - Vilakazi, Busisiwe; Mafongoya, Paramu L.; Odindo, Alfred O.; Phophi, Mutondwa M. (Frontiers in Sustainable Food Systems, 2025)
Neglected legumes are fundamental to global food systems, contributing to agricultural sustainability, enhancing food security, and strengthening the resilience of smallholder farming systems. However, they remain underutilized and have historically received limited attention in terms of cultivation, research, and market development, despite their significant nutritional, agronomic, and environmental potential. This study assessed socioeconomic factors influencing farmers’ willingness to cultivate neglected legumes and their selection of suitable planting dates in Bergville, South Africa. A simple random sampling procedure was employed to collect data from 150 farmers specializing exclusively in crop production. An action research design was implemented, comprising structured training sessions on neglected legumes and trial demonstrations. Data were collected through a structured survey questionnaire, focus group discussions, and key informant interviews. Descriptive statistics were used for analysis, and a multivariate probit model was employed to determine the socioeconomic factors influencing farmers’ willingness to cultivate neglected legumes including Bambara groundnut (Vigna subterranea), cowpea (Vigna unguiculata), pigeon pea (Cajanus cajan), and common bean (Phaseolus vulgaris) and their selection of suitable planting dates. Findings confirmed that the majority of smallholder farmers primarily focus on vegetable cultivation, followed by cereals, while a smaller proportion engage in legume farming. The results also revealed that limited knowledge and resources, along with the lack of training programs and extension services specifically targeting neglected legumes, are significant barriers hindering their adoption and cultivation in the region. Furthermore, the study showed that training on legumes, marital status, farm size, market access, and water sources for irrigation were significant socioeconomic factors influencing farmers’ willingness to cultivate neglected legumes, while household size, legume training, and water sources for irrigation had a significant effect on farmers’ selection of suitable planting dates. These findings underscore the need for targeted interventions, including tailored training programs, improved access to resources, and enhanced extension services, to overcome these barriers and promote the adoption of neglected legumes into smallholder farmers’ cropping systems.